A comment on "A validation of dynamic hygrothermal model with coupled heat and moisture transfer in porous building materials and envelopes". (15th April 2022) - Janssen, Hans
Abstract: In 2020, this journal published the paper "A validation of dynamic hygrothermal model with coupled heat and moisture transfer in porous building materials and envelopes", reporting the verification, validation and confrontation of the Künzel and Liu models for heat and moisture transfer in building materials. This comment formulates several concerns on this work, mainly regarding the material properties applied but also concerning the temporospatial discretisations employed. Firstly it is demonstrated that the Künzel and Liu models are actually very similar concerning the heat and moisture storage and transport mechanisms considered. That development equally reveals an incorrect interpretation of the moisture diffusivity, resulting in faultily doubling the vapour diffusion transport in Künzel's model. Subsequently, it is suggested that the material properties used in the validation exercises are suboptimal and it is also reasoned that the deviating results of the different numerical implementations are not acceptable for a dependable validation. The discusser assumes that repeating the verification and validation exercises with improved material properties and temporospatial discretisations is to reduce the deviations between simulated and calculated/measured (for the verification/validation exercises) results. And since this amends the performance evaluation of the Künzel and Liu hygrothermal models targeted in the commented article, he invites its authors to revisit their study accordingly in their reply to this comment. Highlights: Comment formulates some concerns on a paper previously published in the journal. That paper reported on verification, validation and confrontation of two HAM models. There are concerns on material properties and temporospatial discretisation though. Authors are invited to revisit their study, targeting better performance evaluation.